Specification testing in nonparametric instrumental quantile regression - Christoph Breunig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
There are many environments in econometrics which require nonseparable modeling of a structural disturbance. In a nonseparable model, key conditions are validity of instrumental variables and monotonicity of the model in a scalar unobservable. Under these conditions the nonseparable model is equivalent to an instrumental quantile regression model. A failure of the key conditions, however, makes instrumental quantile regression potentially inconsistent. This paper develops a methodology for testing the hypothesis whether the instrumental quantile regression model is correctly speci ed. Our test statistic is asymptotically normally distributed under correct speci cation and consistent against any alternative model. In addition, test statistics to justify model simpli cation are established. Finite sample properties are examined in a Monte Carlo study and an empirical illustration.
Keywords: 330; Nonparametric quantile regression; instrumental variable; specification test; local alternative; nonlinear inverse problem